2021
DOI: 10.3390/jcm10225334
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life Issues Experienced by Thoracic and Breast Sarcoma Patients: A Rare and Understudied Group

Abstract: Thoracic and breast sarcomas constitute a rare subgroup within the sarcoma population. There is limited knowledge about their health-related quality of life (HRQoL) and a valid disease-specific HRQoL instrument is lacking. This qualitative study aimed to investigate the HRQoL issues experienced by a small group of thoracic and breast sarcoma patients. Semi-structured interviews with 19 thoracic and four breast sarcoma patients were conducted and thematically analysed. Physical issues mentioned by both groups w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…In addition, changes in personality such as being aggressive and grumpy, more emotionally sensitive and less self-confident were described. 34 Disease course and disease development are playing an important role on emotional distress in sarcoma patients. We observed that distress appears to be particularly high in the first months of the disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, changes in personality such as being aggressive and grumpy, more emotionally sensitive and less self-confident were described. 34 Disease course and disease development are playing an important role on emotional distress in sarcoma patients. We observed that distress appears to be particularly high in the first months of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Patients reported fear and anxiety about disease progression or recurrence, were living with uncertainty, experienced changes in mood and negative emotions due to their disease and treatment, and felt angry, sad, tense, down, worried, and depressed. In addition, changes in personality such as being aggressive and grumpy, more emotionally sensitive and less self‐confident were described 34 …”
Section: Discussionmentioning
confidence: 99%
“…Variables such as gender, age, other demographic variables, sarcoma type, surgical procedure, site of cancer, or phase of the disease may also influence QoL and lead to different levels of impairment in sarcoma patients 35,47–50 . The symptoms most reported as disabling were pain 2,39,43,51,52 and fatigue 2,36,43,52 …”
Section: Sarcoma Patientsmentioning
confidence: 99%
“…46 Variables such as gender, age, other demographic variables, sarcoma type, surgical procedure, site of cancer, or phase of the disease may also influence QoL and lead to different levels of impairment in sarcoma patients. 35,[47][48][49][50] The symptoms most reported as disabling were pain 2,39,43,51,52 and fatigue. 2,36,43,52 Survivors of skin sarcomas had the highest scores on global health status, physical functioning, and social functioning; survivors with sarcoma of the axial skeleton reported impairment on all functioning scales except for emotional and cognitive functioning and had the highest scores on the symptom scales except for nausea/vomiting, dyspnea, diarrhea, and financial impact.…”
Section: Quality Of Lifementioning
confidence: 99%